The Effectiveness of Ranitidine Compared to Omeprazole in Maintaining Gastric Acidity in Head Injury Patients - Tjokorda Gde Agung Senapathi (Journal of Global Pharma Technology, 2019)
Background: Gastric bleeding due to stress-related mucosal damage (SRMD) is a condition that is caused due to erosive gastritis that often occurs in critically ill patients in intensive care. One condition that is known as a risk factor for SRMD is traumatic brain injury. Two common agents used as gastric ulcer prophylaxis are proton pump inhibitor (PPI) and H2 antagonist receptor (H2AR). The goal of this study was to compare the effectiveness of PPI and H2AR administration as prophylaxis of SMRD in patients with TBIs who were treated in the ICU. Patients and Methods: This is a single-blind, randomized, controlled trial with pre and post-test measurements. All subjects were measured for baseline gastric pH before being given gastric ulcer prophylaxis. Gastric pH was measured using a pH-meter. The subjects were divided into two groups: omeprazole group (omeprazole 40 mg every 12 hours) and ranitidine group (received ranitidine 50 mg every 12 hours). The pH levels were measured regularly twice daily for five days. Results: 56 subjects were involved in this study and divided equally into two groups. For each gastric pH measurement, the pH in both groups did not significantly differ. The optimal gastric pH was achieved in 24 hours after the first administration of gastric ulcer prophylaxis. Conclusions: The administration of ranitidine or omeprazole is equally effective in maintaining the acidity of gastric acid in TBI patients in ICU. There was no significant difference in the incidence of gastric bleeding in ranitidine and omeprazole groups. Keywords: ICU, Gastric pH, PPI, H2-receptor antagonist.